CROSS-BORDER ACTIVITY OF RESIDENTS OF BORDER REGIONS IN THE EUROPEAN UNION (A CASE STUDY OF LITHUANIANS IN THE POLISH BORDER MARKET) - Batyk, Iwona (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: The study analyzes the cross-border activity of Lithuanians in the Polish border market and the sociodemographic factors determining such activity. Methods: A total of 328 respondents participated in interviews conducted from December 2022 to January 2023. Non-parametric tests were used to analyze the data. The research questions included in this study are as follows – Q1: What are the preferred areas of cross-border activity of Lithuanian residents in the Polish border market?; Q2: What socio-demographic factors determine the cross-border activity of Lithuanian residents in the Polish border market? Results: The results show that the respondents were most active in border trade, tourism, and social relations between regional residents. Age, place of residence, and household size had no significant effect on any of the analyzed areas of cross-border activity of Lithuanians in the Polish border market. Education, professional status, and monthly income had a statistically significant effect on cross-border trade activity, while tourism was significantly statistically affected by gender and education. Conclusions: Cross-border activity fosters the development of border trade and tourism, as well as the creation of links between local communities living in border areas that strengthen neighborly relations. Border trade should encourage entrepreneurs to seek innovative and socially responsible practices that support the sustainable economic development of a country or region. The study provides evidence in the context of realizing cross-border activity that supports residents of border regions in adapting to dynamically changing geopolitical conditions.